2018
DOI: 10.1126/science.aan8821
|View full text |Cite
|
Sign up to set email alerts
|

Combined adult neurogenesis and BDNF mimic exercise effects on cognition in an Alzheimer’s mouse model

Abstract: Adult hippocampal neurogenesis (AHN) is impaired before the onset of Alzheimer's disease (AD) pathology. We found that exercise provided cognitive benefit to 5×FAD mice, a mouse model of AD, by inducing AHN and elevating levels of brain-derived neurotrophic factor (BDNF). Neither stimulation of AHN alone, nor exercise, in the absence of increased AHN, ameliorated cognition. We successfully mimicked the beneficial effects of exercise on AD mice by genetically and pharmacologically inducing AHN in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
439
6
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(505 citation statements)
references
References 59 publications
19
439
6
5
Order By: Relevance
“…For example, activation of endogenous neural stem cells by Ascl1 oscillations can generate many new neurons, which may ameliorate neurodegenerative diseases such as Alzheimer disease and Huntington disease (Benraiss et al, 2013;Choi et al, 2018). For example, activation of endogenous neural stem cells by Ascl1 oscillations can generate many new neurons, which may ameliorate neurodegenerative diseases such as Alzheimer disease and Huntington disease (Benraiss et al, 2013;Choi et al, 2018).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…For example, activation of endogenous neural stem cells by Ascl1 oscillations can generate many new neurons, which may ameliorate neurodegenerative diseases such as Alzheimer disease and Huntington disease (Benraiss et al, 2013;Choi et al, 2018). For example, activation of endogenous neural stem cells by Ascl1 oscillations can generate many new neurons, which may ameliorate neurodegenerative diseases such as Alzheimer disease and Huntington disease (Benraiss et al, 2013;Choi et al, 2018).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…BDNF, a downstream gene of cAMP signaling, mediated by CREB, is a well‐known regulator in modulating synaptic transmission and plasticity, memory development, and storage . It is also well established to have properties of antagonizing neuronal apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…These processes have been demonstrated as important for the induction and persistence of long‐term memory and long‐term potentiation . In addition, the pCREB can also regulate the expression of downstream apoptosis‐associated proteins, including Bcl‐2, Bax, caspase‐3, caspase‐8, and brain‐derived neurotrophic factor (BDNF), which have been found to promote the apoptosis of neurons, and share an association with aggravating cognitive dysfunction . Our previous studies showed that Mn exposure impaired hippocampus‐dependent cognitive function and reduced cAMP signaling and the protein levels of BDNF in occupational Mn‐exposed workers and chronic Mn‐treated rats .…”
Section: Introductionmentioning
confidence: 99%
“…Different exercises are believed to be accompanied by distinct activities of sensory motor circuits to affect neuronal plasticity. Furthermore, there is accumulating evidence that different types of physical exercises such as forced and voluntary running can affect recovery from motor or memory dysfunction (Choi et al, ; Cotman, Berchtold, & Christie, ; So et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is accumulating evidence that different types of physical exercises such as forced and voluntary running can affect recovery from motor or memory dysfunction (Choi et al, 2018;Cotman, Berchtold, & Christie, 2007;So et al, 2017).…”
Section: Introductionmentioning
confidence: 99%